Tuning Triplet-Pair Separation versus Relaxation Using a Diamond Anvil Cell - Grayson S. Doucette; Haw-Tyng Huang; Jason M. Munro; Kyle T. Munson; Changyong Park; John E. Anthony; Timothy Strobel; Ismaila Dabo; John V. Badding; John B. Asbury (Cell Reports Physical Science, 2020)
Summary: A tradeoff exists between triplet-pair separation versus relaxation that can limit the ability to utilize singlet fission for enhancing solar cell efficiency beyond the Shockley-Queisser limit. Here, we show that this tradeoff can be avoided in crystalline environments by studying a functionalized pentacene compressed in a diamond anvil cell. We demonstrate, using ultrafast transient absorption spectroscopy, that there is a “sweet spot” where the rate of triplet-pair separation can be accelerated by nearly an order of magnitude without causing fast excited state relaxation. X-ray diffraction and computational modeling allow us to quantify the corresponding increase of intermolecular coupling. Our findings suggest that increased coupling enhances excited state relaxation but that crystalline environments can suppress these relaxation processes in pentacene derivatives. The combination of these effects leads to the sweet spot and informs efforts to enhance triplet-pair separation rates in amorphous systems such as polymers.